Peningkatan Keterampilan Menulis Karangan Narasi dengan melalui Media Gambar Seri pada Siswa Kelas V SDN 145 Inpres Pampangan - Asri Pratiwi; Andi Adam; Maria Ulviani (Departement of Mathematics Education, 2024)
This research aims to find out how the application of series image media can improve narrative essay writing skills in class V students at SDN 145 Inpres Pampangan, Maros Regency. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out in four meetings. The focus of this research is 1) Narrative essay writing skills and 2) Use of series image media in class V of SDN 145 Inpres Pampangan Maros Regency. Research procedures include planning, implementing actions, observing and reflecting. The research subjects were 16 class IV students. The collected data was analyzed using quantitative and qualitative analysis. The results of this research are: (1) In the first cycle, the average value of learning outcomes for Class V students at SDN 145 Inpres Pampangan Maros Regency was obtained, namely 58.7. (2) In the second cycle, the average value of learning outcomes for Class V students at SDN 145 Inpres was obtained. Maros district's exposure is higher, reaching 82.5. The learning completion of class V students at SDN 145 Inpres Pampangan, Maros Regency has also increased. In cycle I, 3 (18.7%) students achieved complete learning, while in cycle II 14 (87.5%) students achieved complete learning and classical learning was achieved. This means that learning completeness in cycle II was achieved classically because the number of students who completed it was more than 80%. Based on the results of the research above, it can be concluded that the skill of writing narrative essays for class V at SDN 145 Inpres Pampangan Maros Regency through the application of series image media has increased.